2015
DOI: 10.1016/j.applthermaleng.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state modeling and analysis of a loop heat pipe under gravity-assisted operation

Abstract: Abstract:In this paper, a steady-state mathematical model of a loop heat pipe (LHP) in gravity-assisted operation has been established based on two driving modes: gravity driven mode and capillarity-gravity co-driven mode. The modeling results show good agreement with experimental data, and the operating characteristics of the LHP under gravity-assisted attitude has been theoretically investigated. When the heat load applied to the evaporator is smaller than the transition heat load, the LHP is operating in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…For a given heat load and sink temperature, the operating temperature will also keep almost the same. The above trend is similar with the situation in terrestrial gravity reported in reference [16,22,23].…”
Section: Operation At Centrifugal Force Driven Modesupporting
confidence: 91%
See 3 more Smart Citations
“…For a given heat load and sink temperature, the operating temperature will also keep almost the same. The above trend is similar with the situation in terrestrial gravity reported in reference [16,22,23].…”
Section: Operation At Centrifugal Force Driven Modesupporting
confidence: 91%
“…Based on the principle of LHP operation in gravity [2,16,23], the total pressure drop of the loop includes the viscous pressure drops in vapor groove, vapor line, condenser, liquid line and wick. It is recognized that if the entire loop is not in a horizontal plane, an additional pressure head applies due to gravity and it could increase or decrease the total pressure drop.…”
Section: Operating Principle Under Acceleration Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A steady-state model introduced by Bai et al [73] is further improved in later publications [74]- [76]. More sophisticated versions of the model include the analysis of the thermal conductivity of compound wicks and the effect of gravity on the evaporator.…”
Section: Chapter 4: Steady-state Modelmentioning
confidence: 99%